Chromogranin A as a Biochemical Marker for Neuroendocrine Tumors: A Single Center Experience at Royal Hospital, Oman - Elham S. Al-Risi (Oman Medical Journal, 2017)
Objectives: To evaluate the significance of serum chromogranin A (CgA) status in patients with and without different neuroendocrine tumors (NETs) by conducting a retrospective assessment of the diagnostic utility and limitations of CgA as a biomarker for NETs in a tertiary care hospital in Oman. Methods: We conducted a retrospective analysis of CgA requests referred to the Clinical Biochemistry Laboratory, Royal Hospital, Oman over a 24-month period (April 2012 to March 2014). During this time, 302 CgA tests for 270 patients (119 males and 151 females; age range 11–86 years and mean±standard deviation (SD) 44.0±18.0 years), were requested. Of these CgA tests, 245 tests were performed for 245 patients investigated for the diagnosis of NETs, and 57 CgA tests were performed for 25 patients with diagnosed NETs who were undergoing follow-up. Serum CgA levels were analyzed using the enzyme-linked immunosorbent assay based on a cut-off value of 22 IU/L. Results: Of the 302 CgA tests reviewed, 197 (65.2%) were within the quoted normal range; however, 105 (34.8%) had CgA > 22 IU/L. Of the 245 patients with first-line CgA, 38 patients (15.5%) had NET that included carcinoid, pheochromocytoma, pancreatic NET, adrenal adenoma, prostatic adenocarcinoma, gastrointestinal NET, medullary thyroid carcinoma, Schwannoma, lung small cell carcinoma, parathyroid adenoma, and pituitary macroadenoma. The mean±SD of CgA in these patients with NETs was 205.0±172.0 IU/L. Meanwhile, there were 45 (18.3%) patients with CgA > 22 IU/L (83.0±116.0 IU/L) who did not have NETs. The conditions/diseases included: essential hypertension, chronic kidney disease, heart failure, peptic ulcer, chronic diarrhea, use of proton pump inhibitors, and other chronic diseases (hypothyroidism, asthma, diabetes mellitus). Of the 25 patients with known NET who were followed-up, there were 57 CgA results (29 with CgA ≤ 22 IU/L and 28 with CgA > 22 IU/L). The overall clinical sensitivity of CgA in the diagnosis of NETs was 84.2%, overall specificity was 78.2%, positive predictive value was 41.5%, negative predictive value was 96.4%, and overall efficiency was 79.2%. In patients with individual NET, a good reflection in CgA was noticed in the follow-up period following surgery or therapy. Conclusions: Serum CgA is a sensitive and effective noninvasive laboratory test for the clinical detection and management of NETs. Awareness of the pitfalls of the tests in patients with non-NET conditions, particularly chronic diseases and use of certain drugs, is important to be considered during the interpretation of the CgA levels.